PRODUCTION AND EVALUATION OF AUTOGENOUS VACCINE AGAINST AVIAN COLIBACILLOSIS - J. K. El Jakee; G. M. El Amry; A. M. Hessain; H. A. Hemeg S. M. Shafei; I. M. Moussa (Journal of Animal and Plant Sciences, 2016)
The present investigation aimed to prepare a potent Escherichia coli vaccine to control colibacillosis in chickens. Firstly a total of 7 Escherichia coli isolates: O125: K 70, O1: K-, O146: K-, O26: K: –, O 78: K 80, O126: K58 and O128: K 67 were collected from diseased chickens. The collected strains were examined for virulent genes (stx1, stx2, eaeA and hylA) using PCR and analyzed by SDS-PAGE. Inactivated whole culture and outer membrane protein (OMP) vaccines were developed from Escherichia coli serogroups O1 and O78 and determined their potency to induce antibody response against colibacillosis in comparison to Nobilis® vaccine using Micro-agglutination test (MAT) and Enzyme Liked Immunosorbent assay (ELISA). The prepared inactivated and Escherichia coli outer membrane protein vaccines were free from bacterial and fungal contamination and both of the vaccines were found safe with no clinical symptoms when inoculated subcutaneously with double field dose into chicks. The protection rate of the inactivated vaccine was 84%, the protection rate in Nobilis® E. coli inactivated vaccine was 80% and the protection rate in OMP vaccine was 92%. Meanwhile, the mortality rate was 28% among the unvaccinated chicken. The results of this study indicate the higher protection rate of OMP and suggesting further development of OMP as a vaccine for protection of chickens against E. coli infections.
Keywords: Escherichia coli; Vaccine; Outer membrane proteins (OMP); ELISA; Virulent genes